Development of Nutrient Solution Compositions for Paprika Cultivation in a Closed Coir Substrate Hydroponic System in Republic of Korea’s Winter Cropping Season - Kyung-Hwan Yeo; Gyeong-Lee Choi; Jae-Han Lee; Kyung-Sub Park; Ki-Young Choi (Horticulturae, 2023)
Other than in highland areas, the majority of paprika growers in Republic of Korea transplant during late summer and cultivate when temperatures are relatively low. Additionally, they typically apply European nutrient solutions and hydroponic technologies with different climates and cultivation periods. Therefore, this study was conducted to determine the optimal nutrient solution composition based on growth stages suitable for paprika (Capsicum annum L.) cultivation in closed hydroponic systems with a coir substrate during the winter cropping season. The nutrient solutions were supplied to all the paprika plants at pH 5.8–6.0 and electrical conductivity (EC) 2.0–3.5 dS·m−1 according to the target EC setting for each growth stage. The mixing ratio of the reused nutrient solution (drainage) to the fresh solution was maintained within 30% on an EC basis (0.6–1.1 dS∙m−1) at each irrigation event. Paprika plants ‘Cupra’ were grown in three different nutrient solutions using an automated fertilizer dosing system based on integrated solar radiation (ISR). Nutrient absorption patterns according to growth stages were investigated for each nutrient solution. To reduce the nutritional imbalances of major nutrients in the root zone (RZ, substrate), the nutrient solution ‘NIHHS (National Institute of Horticultural and Herbal Sciences)’ was adjusted considering the nutrition absorption patterns according to growth stages, ion balances between anions and cations, and differences between the ion concentrations in the RZ and with irrigation. NIHHS-Coir1 and NIHHS-Coir2 solutions with 5–10% and 10–15% readjustments of macronutrient concentrations in the NIHHS, respectively, were used to evaluate the suitabilities for cultivation and productivity, whilst the IKC (Informatie en Kennis Centrum) nutrient solution was used as the control. We investigated the influence of these solutions on growth, yield, and photosynthetic responses compared to the conventional nutrient solution. Throughout the entire cultivation period, the newly formulated NIHHS-Coir1 solution had a marketable fruit ratio (%) of 2.4–3.5% higher and a marketable yield (kg/m2) of 5.3–8.7% higher than those of the conventional IKC solution.